Tamanho de parcela e número de repetições em aveia branca - Lavezo, André (2016)
The study aimed to determine the optimum plot size (Xo) and the number of repetitions to evaluate fresh mass (FM), dry matter (DM) and grain yield (PROD) of oat and check the variability of Xo between cultivars and sowing dates. For this, were evaluated four cultivars (URS Charrua, URS Taura, URS Estampa and URS Corona) in three sowing times (time 1 – 04/28/2014, time 2 – 5/28/2014 and then 3 – 07/14/2014) in 96 trials uniformity of 3 × 3 m for the determination of Xo in FM and DM variables. The determination of Xo for PROD was necessary 32 uniformity of 3m × 3m tests, eight with each cultivar (URS Charrua, URS Taura, URS Estampa and URS Corona). At flowering were collected plants of tests to obtain FM and DM and heavy, obtaining FM, which were later submitted in air circulation oven forced 65 ± 3°C for 48 hours, after obtained by weighing the DM. At the end of oat crop cycle (the grain ripening stage) grains were collected for determination of PROD (kg ha-1). The optimum plot size (Xo) was determined by the method of maximum curvature of the model coefficient of variation and mean comparison between the evaluation periods and cultivars for the measurement of FM and DM, and among cultivars for measurement of PROD, were compared by the Scott Knott test by bootstrap analysis. In oat, there is variability of Xo among cultivars and sowing dates. For the four cultivars in the three sowing dates, Xo 1.66 m2 and 1.73 m2 they are suitable to assess FM and DM, respectively. Four replications to evaluate up to 50 treatments in a completely randomized designs and random blocks are sufficient for differences between average of 44.75% of the average experiment treatments are significant, by Tukey test (p = 0.05) the variables FM and DM. The Xo of 1,57m2 is sufficient to assess PROD in oat these four cultivars. To assess PROD with up to 50 treatments, the DIC and DBA, four replications are sufficient for differences between average of 40.53% of the average experiment treatments are significant, by Tukey test at 5% probability.